Factors driving the adoption of organic tea farming in the northern region of Bangladesh - Foyez Ahmed Prodhan; Md. Safiul Islam Afrad; Md. Enamul Haque; Muhammad Ziaul Hoque; Mohammed Rokonuzzaman; Hasiba Pervin Mohana; A. K. M. Kanak Pervez (Research in Globalization, 2023)
Tea is a regular export item for Bangladesh, but due to slow growth in production, the country's tea exports have declined. However, organic tea has a great future in this regard. Exploring the underlying factors for the adoption of organic tea farming has great potential for the development of tea production in a sustainable manner. Therefore, our main objective was to identify factors influencing tea growers' attitudes, perceptions, and adoption of organic tea farming in the Panchagarh district of Bangladesh. We adopted the Theory of Planned Behavior (TPB) to investigate the underlying factors affecting the farmers' belief in the adoption of organic farming were measured based on control factors (marketing factors and cost and benefit factors), attitude towards organic farming, and social factors (extension factors) through a binary logistic regression model. Results of this study revealed that organic growers had a more favorable perception, which was significantly different from non-organic growers reading of various factors related to organic farming. Our results demonstrated that education and knowledge significantly influence the farmers to form a highly favorable attitude towards organic tea farming, which together explained 20.6 percent (R2 = 0.206) of the overall variance. Moreover, attitudes towards organic farming and cost-benefit (CBF) factors had a significant impact on the adoption of organic tea farming. Results also revealed that the predicted adoption probability was found to be higher among those farmers who had a highly favorable attitude and a high perceived CBF level towards organic farming. Finally, based on the findings, we concluded that a participatory extension program to enhance the level of knowledge related to organic tea farming could significantly impact farmers' attitudes and behaviors towards the practice of organic tea farming.
Keywords: 330; Adoption; Attitude; Farmers' belief; Organic tea farming; Theory of Planned Behavior